Blood pressure cuffs as a vector for transmission of multi‐resistant organisms: Colonisation rates and effects of disinfection. (20th May 2013) - Grewal, Harjeet; Varshney, Kavita; Thomas, Lee C; Kok, Jen; Shetty, Amith
Abstract Objective Blood pressure (BP) cuffs are potential vectors for transmission of multi‐resistant organisms (MROs). The present study aims to determine MRO colonisation rates in BP cuffs from areas of high patient flow as an assessment of the quality of disinfection and infection control practices. Methods BP cuffs in the ED, high dependency unit (HDU) and operating theatres (OT) were prospectively examined after routine disinfection procedures. Swabs collected from the inner and outer surfaces of BP cuffs during inter‐patient intervals were plated onto replicate organism detection and counting, methicillin‐resistant Staphylococcus aureus (MRSA) and vancomycin‐resistant Enterococcus (VRE) chromogenic agar plates to detect rates of bacterial, MRSA and VRE colonisation, respectively. Results High bacterial colonisation rates were detected in BP cuffs from all three areas. BP cuffs from OT were significantly less colonised compared with cuffs from HDU and ED; 76% versus 96% and 100% (P < 0.0001) for inner surfaces and 86% versus 98% and 100% (P < 0.0001) for outer surfaces, respectively. Equivalent or higher bacterial growth was observed on the inner surface compared with outer surface in 54%, 84% and 86% of BP cuffs from OT, HDU and ED, respectively. MRSA was detected in 3 of 150 (2%) swabs collected, but no VRE was detected. Conclusion Although MRSA and VRE were infrequently isolated, current disinfection and infection control protocols need to be improved given the greater recovery of organisms from the inner compared with outer surfaces of BP cuffs.